1989
DOI: 10.1364/ol.14.001008
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a train of fundamental solitons at a high repetition rate in optical fibers

Abstract: By adiabatic amplification of a periodically modulated cw signal in an optical fiber, a train of approximately independent solitons can be generated at a high repetition rate (up to the terahertz range). These pulse trains can be produced with fibers having slowly varying dispersion as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(58 citation statements)
references
References 14 publications
2
55
0
1
Order By: Relevance
“…(1) Physics Department, Technion, Haifa 32000, Israel (2) Physics Department, Universität Osnabrück, 49069 Osnabrück, Germany (3) Physics Department, Princeton University, Princeton, NJ 08544, USA (4) Department of Electrical Engineering, Princeton University, Princeton, NJ 08544, USA (5) Electrical Engineering and Computer Science Dept., Lehigh University, Bethlehem, PA 18015, USA Modulation Instability (MI) is a universal process that appears in most nonlinear wave systems in nature. Because of MI, small amplitude and phase perturbations (from noise) grow rapidly under the combined effects of nonlinearity and diffraction (or dispersion, in the temporal domain).…”
Section: )mentioning
confidence: 99%
“…(1) Physics Department, Technion, Haifa 32000, Israel (2) Physics Department, Universität Osnabrück, 49069 Osnabrück, Germany (3) Physics Department, Princeton University, Princeton, NJ 08544, USA (4) Department of Electrical Engineering, Princeton University, Princeton, NJ 08544, USA (5) Electrical Engineering and Computer Science Dept., Lehigh University, Bethlehem, PA 18015, USA Modulation Instability (MI) is a universal process that appears in most nonlinear wave systems in nature. Because of MI, small amplitude and phase perturbations (from noise) grow rapidly under the combined effects of nonlinearity and diffraction (or dispersion, in the temporal domain).…”
Section: )mentioning
confidence: 99%
“…The operation of the tapered fiber is equivalent to providing adiabatic amplification, the action of which is to slowly compress solitons with no energy loss to dispersive waves. In their seminal work, Zabusky and Kruskal 118 had shown that sinusoidal waves would evolve into solitary wave plus a dispersive wave component, while Hasegawa and Kodama 116 had shown that a pulse of any reasonable shape and energy would evolve into a soliton; however, Dianov et al 119 were the first to propose the application of a dispersion decreasing optical fiber to adiabatically convert a sinusoidal optical beat signal from two closely frequency-spaced laser sources into a train of fundamental solitons that exhibited no dispersive wave component and that was experimentally realized by Mamyshev et al 120 The parameters of the dispersion decreasing tapered optical fiber must be carefully chosen to allow input pulse compression at the chosen repetition rate, while the ratio of the input to output dispersions effectively sets the compression ratio obtained. The upper repetition rate is limited by the input peak/average power requirements set by the soliton power at launch.…”
Section: Sources Based Upon Adiabatic Soliton Compressionmentioning
confidence: 99%
“…When the overlapping pulses further propagate through the amplifier subject to the combined effects of non-linearity, normal dispersion and adiabatic Raman gain, the oscillation reshapes into a train of dark solitons [26]. Such a reshaping effect has been previously exploited in the spatial field with the transformation of a periodic sinusoidal modulation into a spatial array of dark solitons [27].…”
Section: Generation Of High-repetition Rate Trains Of Dark Solitonsmentioning
confidence: 99%